(untitled) (Academia Science Repository, 2023)
The process of privatizing state banks in Uzbekistan and the potential benefits and challenges associated with this process are discussed in this article. The privatization of state banks is seen as a means to improve the competitiveness and profitability of the banking sector, attract foreign investment, create new jobs, and contribute to economic growth in Uzbekistan. The article pays special attention to the issues and challenges that have arisen during the privatization process, including political resistance and financial stability concerns. The potential impact of privatization on the Uzbek economy, including its potential to spur economic growth, create new jobs, and attract foreign investment, as well as the risks and potential benefits associated with this process, are also discussed.